Analysing the security threats against network convergence architectures - ARGYROUDIS, PATROKLOS; DOYLE, LINDA; O'MAHONY, DONAL EDWARD (IEEE Computer Society Press, 2007)
Current research trends in networks and telecommunications suggest that future architectures will aim for the convergence not only of fixed and mobile infrastructures, but also of different network layer technologies. Proposals like OCALA from UC Berkeley and our own TRANSIT can be used to converge different architectures and network layer overlays while supporting legacy applications. In this paper we analyse and assess the security threats against such systems. Our contribution constitutes the first step in designing security models for convergence architectures as part of their design and deployment phases, rather than as retrofitted mechanisms
Proceedings of the Third International Symposium on Information Assurance and Security (IAS 2007)
Third International Symposium on Information Assurance and Security (IAS 2007)
PUBLISHED
Manchester, United Kingdom
Keywords: network convergence